Management of burn patients at the Hospital Universitario del Valle, Cali, Colombia - Ferrada D., Ricardo; Narváez, Fernando (Colombia Medica, 1987)
From July 1st, 1984, to June 30, 1985, 315 patients with skin burns were attended at the Hospital Universitario del Valle, Cali, Colombia. The management and treatment results are analyzed. Most cases occurred in children, and the accident was household in the majority. Coagulation treatment is a topic, and the management of infections is described.